Clinical and Imaging Response to Trigeminal Schwannoma Radiosurgery: A Retrospective Analysis of a 28-Year Experience - Niranjan, Ajay; Raju, Sudesh S.; Kano, Hideyuki; Flickinger, John C.; Lunsford, Lawrence Dade (Journal of Neurological Surgery Part B: Skull Base, 2020)
Objective The purpose of this study was to evaluate long-term clinical outcomes and tumor control after stereotactic radiosurgery (SRS) for trigeminal schwannoma (TS).Methods During a 28-year period (1989–2017), 50 patients underwent SRS for TS. The median patient age was 51 years (range: 15–87 years). A total of 17 patients had a previous tumor resection: 10 had a single procedure, 5 had two procedures, and 2 had three procedures. The median and mean times between tumor resection and SRS were 12 and 24 months (range: 1–90 months), respectively. Four patients had neurofibromatosis II (NF2). Based on location, tumors were classified as root type (7), ganglion type (22), or dumbbell type (21). The median radiosurgery target volume was 3.4 cm3 (range: 0.10–18 cm3), median target dose was 14 Gy (range: 12–20 Gy), and the median number of isocenters was 6 (range: 1–15). The median and mean times to last follow-up was 36.9 and 55.2 months (range: 4–205 months), respectively. Eighteen patients (36%) had longer than 5-year follow-up, and seven patients (14%) had longer than 10-year follow-up.Results The tumor control rate was 92% and the clinical improvement or stabilization rate was 94%. After SRS, the rates of progression free survival (PFS) at 1, 5, and 10 years were 98, 84, and 84%, respectively. Factors associated with improved PFS were female sex (p = 0.014) and smaller tumor volume (p = 0.022). In this series, we did not find that tumor type (root, ganglion, and dumbbell) had a statistically significant correlation to PFS. Forty-seven patients had neurological signs or symptoms at presentation. At last follow-up, neurological signs or symptoms improved in 22/47 (47%), remained unchanged in 24/50 (48%), and worsened due to tumor progression in 3/50 (6%). One patient (2%) developed temporary symptomatic adverse radiation effect (ARE) and three additional patients (6%) had transient imaging evidence of peritumoral reactive edema but no new symptoms.Conclusion As a single outpatient procedure, SRS was associated with long-term freedom from additional management in 84% of patients. Nearly half the treated patients experienced improvement in neurological symptoms or signs.
Keywords: stereotactic radiosurgery; gamma knife; trigeminal schwannoma